Presence of Noroviruses and Other Enteric Viruses in Sewage and Surface Waters in The Netherlands - Lodder, W. J. (American Society for Microbiology, 2005)
Since virus concentrations in drinking waters are generally below the detection limit, the infectious risk from drinking water consumption requires assessment from the virus concentrations in source waters and removal efficiency of treatment processes. In this study, we estimated from reverse transcription-PCR on 10-fold serially diluted RNA that noroviruses, the most prevalent waterborne gastroenteritis agents, were present at 4 (0.2 to 38) to 4,900 (303 to 4.6 × 10(4)) PCR-detectable units (PDU) per liter of river water (ranges are given in parentheses). These virus concentrations are still high compared with 896 to 7,499 PDU/liter of treated sewage and 5,111 to 850,000 PDU/liter in raw sewage. Sequencing analyses designated human norovirus GGII.4 Lordsdale as the most prevalent strain in the sampling period 1998 to 1999 in both sewage and surface waters. Other GGII strains were also very abundant, indicating that the majority of the virus contamination was derived from urban sewage, although very divergent strains and one animal strain were also detected in the surface and sewage waters. Rotaviruses were also detected in two large rivers (the Maas and the Waal) at 57 to 5,386 PDU/liter. The high virus concentrations determined by PCR may in part be explained by the detection of virus RNA instead of infectious particles. Indeed, reoviruses and enteroviruses that can be cultured were present at much lower levels, of 0.3 to 1 and 2 to 10 PFU/liter, respectively. Assuming 1% of the noroviruses and rotaviruses to be infectious, a much higher disease burden than for other viruses can be expected, not only because of the higher levels but also because of these viruses' higher infectivity and attack rates.